2007
DOI: 10.2176/nmc.47.448
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Survey of the Etiology and Associated Conditions of Prenatally and Postnatally Diagnosed Congenital Hydrocephalus in Japan

Abstract: A nationwide survey in 2000 investigated the causative and associated central nervous system (CNS) lesions of congenital hydrocephalus in Japan. The etiology and associated diseases in 393 patients with congenital hydrocephalus were analyzed and compared between 193 patients with prenatally diagnosed (fetal) hydrocephalus and 181 with postnatally diagnosed (infantile) hydrocephalus. Of 393 patients of congenital hydrocephalus, 355 (90.3%) had primary hydrocephalus and 28 (7.1%) had secondary hydrocephalus. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
3
0
5
Order By: Relevance
“…Cysts and cephaloceles are known causes of hydrocephalus 29, 30 , but the pathogenesis of these malformations is poorly understood. Simple cysts have been attributed to accidental entrapment of CSF within a split layer of arachnoid 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Cysts and cephaloceles are known causes of hydrocephalus 29, 30 , but the pathogenesis of these malformations is poorly understood. Simple cysts have been attributed to accidental entrapment of CSF within a split layer of arachnoid 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial arachnoid cysts are a well-recognized cause of hydrocephalus [62, 63]. Small, simple cysts have been attributed to an entrapment of CSF within the meninges[64], which could conceivably be a developmental accident.…”
Section: Hydrocephalus Accompanied By Other Physical Features (Table 2)mentioning
confidence: 99%
“…In this study, 75% of patients suffering from congenital hydrocephalus did not have any associated central nervous abnormalities. A nationwide survey for aetiology of congenital hydrocephalus in Japan also showed that more than 90% of cases with congenital hydrocephalus were not associated with any other central nervous system pathologies [7]. …”
Section: Discussionmentioning
confidence: 99%